AUDIT INTERNAL TERHADAP KEPATUHAN MANAJEMEN PERUSAHAAN - Zeinora Zeinora; Saripah Saripah; Satria Andika Budi Wibawa (JABE (Journal of Applied Business and Economic), 2022)
This study aims to determine the influence of internal audit on company management compliance. The population in this study were all company employees at PT AGM and PT TIV. Sampling of this research is through purposive sampling technique and obtained 50 respondents as a sample. The analysis technique used in this research is simple regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. based on the results of the calculation of the hypothesis test, it is known that there is an influence of internal audit on company management